Information visualization from the public utilities databases of local municipality for municipalities managers - Savoska, Snezana; Loshkovska, Suzana; Dimitrovski, Ivica (IEEE, 2008)
In this paper, we present the advantages from the use of data visualization from information systems of communal arrangement department for the local selfmanagement. This approach will provide help to the users to analyze and see information more quickly and more efficiently. These visual representations are expected to shorten required time for data analyses. In the paper, we present several visualizations of the integrated data for managers and analytical staff in the local municipality in a city in Republic of Macedonia where the one-stop-shop system is still not implemented.
Keywords: Visualization, Local Municipality Information System, Data Warehouse